ADSORPTION OF METHYLENE BLUE DYE ON ACTIVATED CARBON OBTAINED FROM THE FRUIT OF PLANE TREES - Dodevski, V.; Kaluđerović, B.; Krstić, S.; Čokeša, Đ.; Brković, D. (Journal of Engineering & Processing Management, 2016)
The fruit of plane trees is used to obtain the powdered activated carbon. As the activating agent is used in the preparation of concentrated phosphoric acid. Completed the equilibrium adsorption of cationic methylene blue dye in the synthesized material. These results were fitted with three adsorption equilibrium model. The experimental results were analyzed by the Langmuir isotherm, Freundlich isotherm in the Temkin isotherm. The best fit of the experimental results with theoretical models is obtained in the case of Langmuir’s equilibrium models. According to the Langmuir model, achieved the best adsorption capacity of the adsorbent color which is 354.60 mg g-1 when activated carbon treated with NaOH.